Indeks Penulis Volume 28, Tahun 2008 - Indeks Penulis Volume 28, Tahun 2008 (agriTECH, 2008)
Abdullah, K. 137Ainuri, M. 120Anwar, C. 34Arif, S. S. 130Astuti, M. 34Cahyanto, M. N. 28, 63Caturryanti, D. 70Chayati, I. 9Damat. 63Dewi, Y. S. K. 91Dominika. 91Gardjito, M. 15, 174Hardono, E. 120Haryadi. 63Indrati, R. 50, 162Irawadi, T. T. 120Kanetro, B. 50Khairina, R. 186Khotimah, I. K. 186Kurniawan, J. 130Kurniawan, M. P. 58Kusuma, S. A. 113